Constraints perceived by dairy farmers of irrigated and rainfed areas of Visakhapatnam district of Andhra Pradesh (Indian Journal of Animal Production and Management, 2024)
A survey was conducted to assess the constraints perceived by the dairy farmers in irrigated and rainfed  areas of Visakhapatnam district of Andhra Pradesh. The data on constraints perceived by 200 dairy farmers  from 50 different villages were collected by using a pretested questionnaire through personal interviews  and were analysed. The high cost of purebred buffaloes and crossbred cows, the non-remunerative price  for milk, the high cost of feed ingredients and the high incidence of repeat breeding in dairy animals were  found to be the major constraints felt by the dairy farmers in the study area. More technical services, inputs  and extension services are to be provided to the milk producers in both irrigated and rainfed are as to  increase the adoption of the best feeding and management practices in dairy animals of the study area.
Keywords: Constraints; Dairying; Dairy farmers; Irrigated; Rainfed